ANALISIS FUNGSI STRATEGIS DAN TIPE-TIPE KEPEMIMPINAN PENDIDIKAN ISLAM DI ERA MODERN - Aida Nurul Hikmah; Yuliana (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
Leadership is a key element in determining the direction and success of an organization. This study aims to identify the functions and types of leadership that play a role in organizational effectiveness, especially in the context of education. A descriptive qualitative approach is used with a literature study as the main method to explore relevant leadership theories. The results of the study indicate that leadership functions include planning, organizing, directing, and controlling. In addition, there are various types of leadership that are commonly applied, including authoritarian, democratic, and laissez-faire leadership. Each type has different characteristics and influences on the motivation, communication, and productivity of organizational members. This study emphasizes the importance of choosing the type of leadership that is appropriate to the situation, organizational culture, and characteristics of the individuals being led. By understanding the functions and types of leadership properly, a leader can carry them out optimally to achieve organizational goals. This study is expected to contribute to the development of leadership insights, especially for practitioners and academics in the field of education.